1985
DOI: 10.1002/cber.19851180332
|View full text |Cite
|
Sign up to set email alerts
|

Synthese, Struktur und thermische Umlagerungen des 2,6‐Dicyan‐1,5‐dimethylsemibullvalens

Abstract: Zinkiodid-katalysierte Addition von Trimethylsilylcyanid an dasThe zinc iodide-catalyzed addition of trimethylsilyl cyanide to the bicyclo[3.3 .O]octane-2,6-dione 9 yields the sterically defined 0-silylated cyanohydrine 10. Trichlorophosphane oxide in pyridine converts the latter to the unsaturated dinitrile 11. Bromination of 11 using N-bromosuccinimide affords the exo,exo-dibromodinitrile 13. The latter is debrominated by zinc/copper to the dicyanosemibullvalene 4a while the dehydrobromination with potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…When the pure solid or a solution of either semibullvalene is cooled, the color decreases in intensity and by about −78 °C the color is greatly diminished. Quast et al observed similar results in their most fluxional semibullvalenes and barbaralanes and have correlated this reversible thermochroism with a very flat double minimum potential energy surface and an exceptionally low activation barrier to the Cope rearrangement 27b…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…When the pure solid or a solution of either semibullvalene is cooled, the color decreases in intensity and by about −78 °C the color is greatly diminished. Quast et al observed similar results in their most fluxional semibullvalenes and barbaralanes and have correlated this reversible thermochroism with a very flat double minimum potential energy surface and an exceptionally low activation barrier to the Cope rearrangement 27b…”
Section: Resultsmentioning
confidence: 66%
“…An alternative for studying the solution-phase properties of semibullvalenes is IR spectrometry. The time scale of the IR experiment renders it more amenable than NMR to the investigation of extremely rapid processes. ,27b,c, The observation of two nitrile bands in the IR spectra of 22 ,27c 26 ,37a 27 ,27b and 28 37b supported the conclusion of Quast et al that these molecules were highly fluxional, but not homoaromatic. It would appear that the carbonyl region of the IR spectrum of 10 could be used in a similar diagnostic manner.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although several nondegenerate semibullvalenes meet these requirements for large temperature dependence of carbon-13 shifts (13)(14)(15), most of them still possess barriers to exchange which are too high, resulting in line broadening and the emerging of the spectra of the nonrearranging valence tautomers at temperatures well above 100 K. The known accelerating effect of suitably placed cyano groups on the degenerate Cope rearrangement of semibullvalene (20) has led us to conceive the pair of valence tautomers 1 ‫-(‬ 1a and 1b), which is also useful in another context (21). It is a stable, crystalline material (m.p.…”
Section: Introductionmentioning
confidence: 97%
“…Many substituted semibullvalenes undergo degenerate Cope rearrangements via transition structures, which may exhibit C 2 , C S , or C 2v symmetry. , There are also semibullvalenes that are completely locked in one of the two possible valence tautomeric structures, e.g., benzosemibullvalenes. , Between these limiting cases, a considerable number of semibullvalenes exist whose Cope equilibria are more or less skewed by virtue of appropriately placed substituents (including monoannelation), , deuterium atoms, or heteroatoms 14 . These nondegenerate semibullvalenes merit renewed interest for several reasons.…”
Section: Introductionmentioning
confidence: 99%